A tool to simplify software log analysis - Pereira, Nuno José Cancela Branco Pinheira (2022)
Log analysis is a necessary, challenging, and time-consuming task for software development and maintenance. As with many fields of Information Technologies, there is an effort in the optimization of the logging process as well as on the analysis of the stored information. There is a severe lack of standardization on the log data representation, which poses challenges on the development of tools for log analysis. Another issue is the size of some log files, that can lead to slow searches. In this work, we develop a standalone log analysis tool. This tool has an intuitive and simple interface, such that it has a small learning curve for the user. For a typical user, its use should be straightforward. The open source tool provides some functionalities for text-based log files, displaying some indicators and graphs. Thus, it allows for the user to quickly locate the origin of the problems within the analysed code. Another testing tool was developed in the context of this work. This tool is a con figurable log file source generator providing the creation of different scenarios for log analysis. Use cases were written for all features, being evaluated and tested, both manually and programmatically.